2019
DOI: 10.1002/cssc.201802645
|View full text |Cite
|
Sign up to set email alerts
|

Scaling Up Electrodes for Photoelectrochemical Water Splitting: Fabrication Process and Performance of 40 cm2LaTiO2N Photoanodes

Abstract: A scalable process for fabrication of particle‐based photoanodes is developed. The electrodes are versatilely made of photocatalytically active semiconductor particles, in this case LaTiO 2 N, and optionally coated with cocatalysts and protecting components, all immobilized on a conducting substrate. The involved fabrication steps are restricted to scalable processes such as electrophoretic deposition, annealing in air, and dip coating. Special care is taken to ensure efficient charge tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 25 publications
(36 reference statements)
0
27
0
Order By: Relevance
“…The good stability is in part enabled by feeding pure water, instead of the strongly acidic or basic electrolytes commonly used in (I)PEC devices. [ 15,16,19,30–35 ] While PEC devices often suffer from significant performance losses during scale‐up (Table S2, Supporting Information), [ 33,35–41 ] our initial assessments suggest that this IPEC device design is scalable without large performance losses and that the results are reproducible. Furthermore, we analyze the material costs of the device, indicating that light concentration may be necessary to offset today's high costs of low‐volume III–V PVs and to achieve the DOE cost target (Tables S3 and S4, Supporting Information).…”
Section: Resultsmentioning
confidence: 97%
“…The good stability is in part enabled by feeding pure water, instead of the strongly acidic or basic electrolytes commonly used in (I)PEC devices. [ 15,16,19,30–35 ] While PEC devices often suffer from significant performance losses during scale‐up (Table S2, Supporting Information), [ 33,35–41 ] our initial assessments suggest that this IPEC device design is scalable without large performance losses and that the results are reproducible. Furthermore, we analyze the material costs of the device, indicating that light concentration may be necessary to offset today's high costs of low‐volume III–V PVs and to achieve the DOE cost target (Tables S3 and S4, Supporting Information).…”
Section: Resultsmentioning
confidence: 97%
“…Finally, we note that our simulation results, which show non-linearity dependence between the electrode area and the total scale-up associated losses, qualitatively agree with experimental results reported in the literature. 21,23,55 Further experiments usingfor examplein situ pH monitoring 56,57 and particle image velocimetry 58 are needed to quantitatively validate our ndings.…”
Section: Discussionmentioning
confidence: 94%
“…Most reported devices have an area of smaller than 1 cm 2 , and only a handful demonstrated areas larger than 10 cm 2 . 2,[19][20][21][22][23] Moreover, these large-area devices tend to deliver much lower STH efficiency (by up to a factor of $5) as compared to their small-area equivalent. 2 For example, it was recently reported that while small-area (0.24 cm 2 ) BiVO 4 -based tandem device delivers STH efficiency of $6%, the large-area (50 cm 2 ) equivalent is only capable of delivering an STH efficiency of $2%.…”
Section: Introductionmentioning
confidence: 99%
“…31 These types of losses have been observed elsewhere in the scale up of metal oxide photoanodes. 32 However, no detailed analysis of the underlying reasons for the lower photocurrent densities for the large area photoanodes (25 and 300 cm 2 ) as compared to the smaller area (1 cm 2 ) was made.…”
Section: Introductionmentioning
confidence: 99%